IDENTIFICATION OF FACTORS INFLUENCING LAND VALUE FOR STATE’S ASSETS MASS APPRAISAL PURPOSES: EVIDENCE FROM INDONESIA - Prasetyo, Kristian Agung; Safitra, Dhian Adhetiya; Swasito, Adhipradana Prabu (PLANNING MALAYSIA, 2021)
Land value is an important element in a decision making. The estimation of land value conducted individually based on comparables. This approach often faces difficulties due to the large quantities of such assets with limited capacity of valuers. This research aimed to build a model to effectively identify the main property attributes that shape property value and quantify the effect of unobserved variables on value. We observed 628 property data in Jakarta collected by the Directorate General of State Asset Management (DGSAM) as part of their valuation activities in 2018. The results of this study provide an evidence that structural equation model (SEM) can be effectively used to identify property attributes that significantly affect property value, particularly for valuing state-owned assets.